Comparative evaluation of the Peng-Robinson equation and its variants Mathias-Copeman and Stryjek-Vera, for pure methane in subcritical regime. - Feroni, Wilson José; Feroni, Rita de Cassia; Romero, Oldrich Joel (Latin American Journal of Energy Research, 2025)
This study evaluates the Peng-Robinson (PR) equation of state and two variants using the Mathias-Copeman (MC) and Stryjek-Vera (SV) alpha correction functions for pure methane, adopting the Setzmann-Wagner ancillary equations as reference. The formulations were implemented in Python to calculate the saturation pressure , the saturated liquid density , and the saturated vapor density . For , a good visual agreement with the reference is observed, and the mean absolute percentage deviations indicate the best overall performance for MC, followed by SV and then PR, although the differences among the curves are small. For , the models show overestimation at low temperatures, with a progressive reduction of the deviation as temperature increases; PR, MC, and SV exhibit very similar trends, but with large deviations relative to the reference. For , the three models remain close to the reference over most of the interval, with a slight advantage for MC and SV, while PR tends to show somewhat larger deviations, without relevant discrepancies.
Keywords: Peng-Robinson; Mathias-Copeman; Stryjek-Vera; Methane; Saturation Pressure